The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1371/journal.pntd.0005334
|View full text |Cite
|
Sign up to set email alerts
|

Unrecognized Emergence of Chikungunya Virus during a Zika Virus Outbreak in Salvador, Brazil

Abstract: BackgroundChikungunya virus (CHIKV) entered Brazil in 2014, causing a large outbreak in Feira de Santana, state of Bahia. Although cases have been recorded in Salvador, the capital of Bahia, located ~100 km of Feira de Santana, CHIKV transmission has not been perceived to occur epidemically, largely contrasting with the Zika virus (ZIKV) outbreak and ensuing complications reaching the city in 2015.Methodology/Principal FindingsThis study aimed to determine the intensity of CHIKV transmission in Salvador betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 27 publications
(34 reference statements)
4
42
0
Order By: Relevance
“…Curiously, ZIKV spread in Salvador was very rapid and the outbreak, comprising ~17,500 case reports, lasted only two months [15,16], while the CHIKV emergence was less abrupt and lasted longer, hampering its prompt recognition, especially because public health attention was directed to the ZIKV outbreak [17]. Although our surveillance study included only one health unit of Salvador, our arboviral detection over time reflected previous citywide observations [15][16][17].…”
Section: Presumptive Diagnosesmentioning
confidence: 53%
See 1 more Smart Citation
“…Curiously, ZIKV spread in Salvador was very rapid and the outbreak, comprising ~17,500 case reports, lasted only two months [15,16], while the CHIKV emergence was less abrupt and lasted longer, hampering its prompt recognition, especially because public health attention was directed to the ZIKV outbreak [17]. Although our surveillance study included only one health unit of Salvador, our arboviral detection over time reflected previous citywide observations [15][16][17].…”
Section: Presumptive Diagnosesmentioning
confidence: 53%
“…Particularly noteworthy was our finding of CHIKV circulation in Salvador at the same time (September 2014) that it was first detected causing outbreaks in other Brazilian cities [3,4], though apparently major amplification in Salvador only began in June 2015, one month after the ZIKV epidemic peak in May 2015 [15]. Curiously, ZIKV spread in Salvador was very rapid and the outbreak, comprising ~17,500 case reports, lasted only two months [15,16], while the CHIKV emergence was less abrupt and lasted longer, hampering its prompt recognition, especially because public health attention was directed to the ZIKV outbreak [17]. Although our surveillance study included only one health unit of Salvador, our arboviral detection over time reflected previous citywide observations [15][16][17].…”
Section: Presumptive Diagnosesmentioning
confidence: 99%
“…To confirm this chikungunya outbreak Polymerase Chain Reaction (PCR) test was done and the positivity rate was 60%. Studies in other countries also showed that, the positivity rates of CHIKV among suspected cases ranges from 12.9% to 75% [1316].…”
Section: Discussionmentioning
confidence: 99%
“…To avoid misdiagnosis based on clinical symptoms only (2), viral RNA was extracted from 140 μL of serum samples using QIAmp viral RNA kit (Qiagen) and RT-qPCR analyses were performed for DENV serotypes 1-4 (3), ZIKV (4) and CHIKV (5). Two additional CHIKV RT-qPCR+ samples from Paraíba were included in subsequent analysis.…”
Section: Articlementioning
confidence: 99%